Development of microbial-fortified rice straw compost for aerobic rice cultivation - Ng, Lee Chuen (2012)
Rice production consumes lots of water. Due to increasing water scarcity,research on aerobic rice cultivation has been intensified. Poor root anchorage,unavailable phosphorus (P), low soil organic matter and blast disease caused by Pyricularia oryzae are the major constraints of aerobic rice cultivation systems.A study was carried out with the aim to inoculate commercially prepared rice straw compost (RSC) with a consortium of microbes in order to produce a microbial-fortified product, and evaluate its bio-efficacy on rice blast severity,growth, yield and soil health of rice variety M4 using an aerobic cultivation system. Four bacterial isolates [Pseudomonas aeruginosa (P1), Corynebacterium agropyri (P7), Enterobacter gergoviae (P9) and Bacillus amyloliquefaciens (S3)] and two Trichoderma spp. [(Trichoderma harzianum (T1) and Trichoderma virens (T2)] isolated from rice rhizospheres have been isolated and selected based on in vitro tests for the production of indole-acetic acid (IAA), siderophore, chitinase, volatile compounds, abilities to solubilize phosphate and suppress mycelia growth of P. oryzae. These isolates were proven to be compatible as a mixed culture. Enterobacter gergoviae, B. amyloliquefaciens, T. harzianum and T. virens had significantly increased seed germination and seedling establishment, due to their ability to produce IAA and solubilize phosphate. Seedlings pre-inoculated with P. aeruginosa, C. agropyri and T. harzianum have higher production of peroxidase, polyphenol oxidase and phenylalanine ammonia-lyase corresponding to lower incidence of blast disease under greenhouse conditions. Total microbial activity based on fluorescein diacetate (FDA) hydrolysis measured in rhizosphere soil was positively correlated (r = 0.76, P = 0.04) to the seedling vigor index. These isolates were further inoculated into commercial rice straw compost (RSC) as carriers. The stability and the survival of the introduced microbes were evaluated based on total culturable plate count and FDA hydrolysis in storage up to 38 weeks. The viability of all the introduced bacteria in the microbial-fortified RSC in both sterilized and non-sterilized conditions decreased with time of storage. At week 38th, in sterilized RSC, all introduced bacteria was detected at 1.00 log10 cfu/g and none of the introduced bacteria was detected in unsterilized RSC. The viability of T. harzianum and T. virens remained constant (5.48–7.78 log10 cfu/g)throughout the storage period and was associated with the better colonization and proliferation due to no competition from the indigenous Trichoderma spp. A greenhouse experiment indicated that soil amended with the microbial-fortified RSC significantly improved yield (1768.42, 1052.00 and 2233.33%) and decreased rice blast severity based on AUDPC (area under disease progress curve) (74.52, 86.31 and 86.70%) compared to the control (mineral soil alone),when P. oryzae inoculated at 14, 56 and 80 DAS (days after sowing),respectively. In soil amended with microbial-fortified RSC also improved soil total microbial activity (4.49 μg/g/0.5h in control; 7.32 μg/g/0.5h in soil amended with microbial-fortified RSC) at harvest, as well as physico-chemical properties included soil EC, bulk density and moisture content. Microbial-fortified RSC introduced during soil preparation was effective in reducing rice blast severity,promoting plant growth, yield and improving soil health for rice variety M4 under aerobic cultivation system.